2018
DOI: 10.1007/s11356-018-1528-y
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability and dengue hemorrhagic fever in Southeast Sulawesi Province, Indonesia

Abstract: To determine the association of climatic factors and dengue hemorrhagic fever and to develop the prediction approach of future dengue transmission. The study used totally monthly dengue hemorrhagic fever cases at Health Office Kendari, Southeast Sulawesi, Indonesia. Monthly meteorological data, consisting of temperature, rainfall, and humidity, was obtained from the Meteorology, Climatology and Geophysics Agency in Kendari district. All data analysis, including Spearman and Poisson distribution, was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
5
22
1
6
Order By: Relevance
“…In Taiwan, temperature and precipitation influenced dengue incidence rates with a lag of 10–20 weeks [ 26 ]. In the context of dengue infection in Indonesia, studies have shown that dengue incidence is associated with temperature, rainfall, and humidity [ 45 , 46 , 47 ]. In this present study, those local climate variables (temperature, rainfall, and humidity), which might have had a stronger impact on chikungunya incidence, were not included.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, temperature and precipitation influenced dengue incidence rates with a lag of 10–20 weeks [ 26 ]. In the context of dengue infection in Indonesia, studies have shown that dengue incidence is associated with temperature, rainfall, and humidity [ 45 , 46 , 47 ]. In this present study, those local climate variables (temperature, rainfall, and humidity), which might have had a stronger impact on chikungunya incidence, were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Rangkaian kata kunci yang digunakan adalah variasi dari "dengue","climate","Indonesia". (Kesetyaningsih, Andarini, Sudarto, & Pramoedyo, 2018a), dua lainnya menggunakan analisis multivariat (Tosepu, Tantrakarnapa, Nakhapakorn, & Worakhunpiset, 2018;Tosepu, Tantrakarnapa, Worakhunpiset, & Nakhapakorn, 2018).…”
Section: Kata Kunciunclassified
“…Nilai temperatur rata-rata dan temperatur maksimal menunjukkan korelasi tinggi pada lag 2-4, sedangkan temperatur minimal pada lag 1-3 dan 5. Di Kolaka, temperatur rata-rata berkisar 26,1-29,7 o C, dengan nilai minimum sebesar 24,2 o C dan maksimum 33,6 o C. Korelasi positif temperatur rata-rata dan maksimal pada lag 2, 3 dan 4, dan temperatur minimum pada lag 0, 1, 2, 3 (Tosepu, Tantrakarnapa, Nakhapakorn, et al, 2018;Tosepu, Tantrakarnapa, Worakhunpiset, et al, 2018).…”
Section: Temperaturunclassified
“…In a small proportion of incidences, the disease develops into severe cases, resulting in bleeding, low levels of blood platelets, and blood plasma leakage or shock syndrome [1]. The dengue virus (five serotypes of the dengue virus) is transmitted by Aedes albopictus and Aedes aegypti [4] and is highly sensitive to environmental factors [5][6][7][8]. Meteorological conditions, such as temperature, precipitation, and humidity, have a significant impact on the spread of dengue fever (DF) as the conditions help to increase the population density of Aedes [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The dengue virus (five serotypes of the dengue virus) is transmitted by Aedes albopictus and Aedes aegypti [4] and is highly sensitive to environmental factors [5][6][7][8]. Meteorological conditions, such as temperature, precipitation, and humidity, have a significant impact on the spread of dengue fever (DF) as the conditions help to increase the population density of Aedes [5][6][7][8]. As temperature and precipitation increase, the stages of development of Aedes larvae to pupa become shorter, thereby increasing the population growth of Aedes [9,10].…”
Section: Introductionmentioning
confidence: 99%